2011
DOI: 10.1203/pdr.0b013e3182055ede
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Pregnancy: Implications for the Mother and Lifelong Health of the Child. A Consensus Statement

Abstract: Obesity among pregnant women is becoming one of the most important women's health issues. Obesity is associated with increased risk of almost all pregnancy complications: gestational hypertension, preeclampsia, gestational diabetes mellitus, delivery of large-for-GA infants, and higher incidence of congenital defects all occur more frequently than in women with a normal BMI. Evidence shows that a child of an obese mother may suffer from exposure to a suboptimal in utero environment and that early life adversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
215
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(228 citation statements)
references
References 62 publications
5
215
0
8
Order By: Relevance
“….Maternal obesity seems to be associated with short-term adverse maternal and fetal outcomes (1)(2)(3)(4)(5). It has also been suggested that maternal obesity is associated with long-term maternal and offspring consequences, such as postpartum weight retention, metabolic syndrome, and obesity in the offspring (1,3,6).…”
Section: Introductionmentioning
confidence: 99%
“….Maternal obesity seems to be associated with short-term adverse maternal and fetal outcomes (1)(2)(3)(4)(5). It has also been suggested that maternal obesity is associated with long-term maternal and offspring consequences, such as postpartum weight retention, metabolic syndrome, and obesity in the offspring (1,3,6).…”
Section: Introductionmentioning
confidence: 99%
“…ECG signal quality was not correlated with BMI, while a correlation was found between CTG signal quality and BMI. This is particularly important because a distinct increase in maternal BMI has been noted in the past few decades [15]. The limitations of this study include the limited numbers of patients and the use of a CTG device from only a single manufacturer.…”
mentioning
confidence: 98%
“…Infants born to overweight and obese women are more likely to suffer fetal macrosomia and shoulder dystocia (22,23,26,27) .…”
mentioning
confidence: 99%